Tet Enzymes Regulate Telomere Maintenance and Chromosomal Stability of Mouse ESCs - Jiao Yang; Renpeng Guo; Hua Wang; Xiaoying Ye; Zhongcheng Zhou; Jiameng Dan; Haiying Wang; Peng Gong; Wei Deng; Yu Yin; ShiQing Mao; Lingbo Wang; et al. (Cell Reports, 2016)
Ten-eleven translocation (Tet) family proteins convert 5-methylcytosine to 5-hydroxymethylcytosine. We show that mouse embryonic stem cells (ESCs) depleted of Tet1 and/or Tet2 by RNAi exhibit short telomeres and chromosomal instability, concomitant with reduced telomere recombination. Tet1 and Tet2 double-knockout ESCs also display short telomeres but to a lesser extent. Notably, Tet1/2/3 triple-knockout ESCs show heterogeneous telomere lengths and increased frequency of telomere loss and chromosomal fusion. Mechanistically, Tets depletion or deficiency increases Dnmt3b and decreases 5hmC levels, resulting in elevated methylation levels at sub-telomeres. Consistently, knockdown of Dnmt3b or addition of 2i (MAPK and GSK3β inhibitors), which also inhibits Dnmt3b, reduces telomere shortening, partially rescuing Tet1/2 deficiency. Interestingly, Tet1/2 double or Tet1/2/3 triple knockout in ESCs consistently upregulates Zscan4, which may counteract telomere shortening. Together, Tet enzymes play important roles in telomere maintenance and chromosomal stability of ESCs by modulating sub-telomeric methylation levels.